Mediasi Kepuasan Kerja pada Motivasi dan Beban Kerja untuk Meningkatkan Kinerja Karyawan - Muhammad Rafif Falah; Ika Korika Swasti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the influence of motivation and workload on performance through job satisfaction. This study was carried out by distributing questionnaires to 50 employees in the marketing division, with statements filled in using a 5 point Likert scale. The data obtained was then analyzed using Partial Least Square (PLS). The result showed that overall performance was influence by motivation and workload through job satisfaction and the rest influenced by other variables outside the research model. Motivation has a significant positive influence on performance and workload has a negative significant influence on performance. On indirect effect, job satisfaction has mediated the two independent variables on the dependent variables. Through job satisfaction, motivation has a significant positive influence on performance and workload through indirect effect has a significant negative on performance.